Polyphenols and exercise in autophagy regulation: potential benefits for cancer management and healthspan - Liu, Wei; Hu, MengDi; Cao, Feng; Jin, Shen (Frontiers in Nutrition, 2025)
Autophagy, a regulated cellular process, serves as both a tumor suppressor and a survival mechanism for tumor cells under stress in cancer. Recent studies demonstrate that polyphenols, bioactive compounds present in plant-derived foods, and exercise, a potent physiological stimulus, can efficiently modulate autophagy in both cancer patients and healthy individuals. This review explores the synergistic effects of polyphenols and exercise in regulating autophagy through key molecular pathways, including AMPK/mTOR, PI3K/Akt, and SIRT1/FOXO. Polyphenols such as quercetin, resveratrol, and curcumin possess autophagy-inducing properties, which may enhance exercise-induced cellular adaptations, contribute to cancer prevention, and improve metabolic health. Moreover, regular physical activity promotes autophagic flux, reducing oxidative stress, inflammation, and apoptosis resistance—factors critical in cancer progression and overall health maintenance. The review highlights the potential of polyphenol-exercise synergy in modulating autophagy, which may result in innovative therapeutic approaches for cancer treatment and metabolic health.